A mechanistic view of drying suspension droplets. Issue 11 (4th February 2016) - van der Kooij, Hanne M.; van de Kerkhof, Gea T.; Sprakel, Joris
Abstract : We unravel the complex mechanisms governing the drying of suspension droplets, both theoretically and experimentally, focusing on the effects of particle deformability. Abstract : When a dispersion droplet dries, a rich variety of spatial and temporal heterogeneities emerge. Controlling these phenomena is essential for many applications yet requires a thorough understanding of the underlying mechanisms. Although the process of film formation from initially dispersed polymer particles is well documented and is known to involve three main stages – evaporation, particle deformation and coalescence – it is impossible to fully disentangle the effects of particle deformation and coalescence, as these stages are closely linked. We circumvent this problem by studying suspensions of colloidal rubber particles that are incapable of coalescing. Varying the crosslink density allows us to tune the particle deformability in a controlled manner. We develop a theoretical framework of the main regimes and stresses in drying droplets of these suspensions, and validate this framework experimentally. Specifically, we show that changing the particle modulus by less than an order of magnitude can completely alter the stress development and resulting instabilities. Scanning electron microscopy reveals that particle deformability is a key factor in stress mitigation. Our model is the suspension equivalent of the widely used Routh–Russel model for film formation in drying dispersions, with additional focus on lateral nonuniformities such as cracking and wrinkling inherent to the droplet geometry, thus adding a new dimension to the conventional view of particle deformation.